2018
DOI: 10.1186/s12864-018-5208-6
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into the genetic basis of buffalo reproductive performance

Abstract: BackgroundFertility is a complex trait that has a major impact on the development of the buffalo industry. Genome-wide association study (GWAS) has increased the ability to detect genes influencing complex traits, and many important genes related to reproductive traits have been identified in ruminants. However, reproductive traits are influenced by many factors. The development of the follicle is one of the most important internal processes affecting fertility. Genes found by GWAS to be associated with follic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 56 publications
1
33
0
2
Order By: Relevance
“…The SNPs in the 90 K SNPChip were selected using buffalo DNA sequence, but similar to methods used in previous studies [1,5,33,[72][73][74][75], were reported according to the location on the cattle reference genome assembly (UMD3.1 [76]) Although chromosome-level assembly of the water buffalo genome (UOA_WB_1) has been published recently [77], we used the UMD3.1 assembly in our study because it is more reliable and has better gene annotation information. Genotypes were obtained through AffyPipe [78], and all the monomorphic and polymorphic SNPs with high resolution (n = 64,750) were stored.…”
Section: Sample Collection Ethical Statement and Data Quality Controlmentioning
confidence: 99%
“…The SNPs in the 90 K SNPChip were selected using buffalo DNA sequence, but similar to methods used in previous studies [1,5,33,[72][73][74][75], were reported according to the location on the cattle reference genome assembly (UMD3.1 [76]) Although chromosome-level assembly of the water buffalo genome (UOA_WB_1) has been published recently [77], we used the UMD3.1 assembly in our study because it is more reliable and has better gene annotation information. Genotypes were obtained through AffyPipe [78], and all the monomorphic and polymorphic SNPs with high resolution (n = 64,750) were stored.…”
Section: Sample Collection Ethical Statement and Data Quality Controlmentioning
confidence: 99%
“…The SNPs in the 90K SNPChip were selected using buffalo DNA sequence, but similar to methods used in previous studies [1,5,33,[72][73][74][75], were reported according to the location on the cattle reference genome assembly (UMD3.1 [76]). Although chromosome-level assembly of the water buffalo genome (UOA_WB_1) has been published recently [77], we used the UMD3.1 assembly in our study because it is more reliable and has better gene annotation information.…”
Section: Sample Collection Ethical Statement and Data Quality Controlmentioning
confidence: 99%
“…The SNPs in the 90K SNPChip were selected using buffalo DNA sequence, but similar to methods used in previous studies [1,5,37,[76][77][78][79], were reported according to the location on the cattle reference genome assembly (UMD3.1 [80]). Although chromosome-level assembly of the water buffalo genome (UOA_WB_1) has been published recently [81], we used the UMD3.1 assembly in our study because it is more reliable and has better gene annotation information.…”
Section: Sample Collection Ethical Statement and Data Quality Controlmentioning
confidence: 99%